The Application of Selective Herbicides to Forestry Practice - Srivastava, T. X. (Indian Forester, 1952)
1. In Part I, some of the general aspects of selective methods of weed control have been discussed in relation to the historical development of the technique, properties, mode of action and methods of application of herbicides in practice. 2. Part II deals with the application and scope of this technique in forestry practice, such as the eradication of undesirable species in the forest and the control of weeds in forest nurseries. 3. Investigations into the herbicidal effects of 3 phenoxy-acetic compounds (Na, M,C.P,A., Na. D,C.P.A., T.C.P.A. ) and I.P.C, on the pre-emergent stages of II tree species (both coniferous and broad-leaved) have revealed varying degrees of toxicity, I.P.C. in general has proved to be less toxic than the phenoxy-acetic compounds; the latter being comparatively more toxic to the broad-leaved species than to the conifers. A comparison of probit lines derived from the mortality figures has indicated a lesser variability in the response of Acacia catechu and Norway pine to concentrations of the phenoxy-acetic compounds than in the case of other species. 4. From investigations into the effects of a variety of herbicides-inorganic, organic, growth substances and petroleum fractions on the post-emergent stages of Scots pine, Sitka spruce and Japanese larch grown in pots and nursery beds, it appears that the lighter oil fractions show the greatest promise for weed control in forest nurseries. Potassium ethyl xanthate with Sitka spruce and Scots pine, Amm. D.N .B.P. with Scots pine and the growth substances are worthy of further trials. The remaining compounds, amm. sulphamate, sodium thiocyanate, sodium pentachloro-phenate, diesel oil and lubricating oil extract have proved too toxic.